Strategies and outcomes of different methods for treating abdominal aortic stent graft infection - Zhang, Mengqiang; Chen, Zhipeng; Tang, Chen; Liu, Cheng; Li, Xiaoqiang; Liu, Zhao; Qiao, Tong (Frontiers in Cardiovascular Medicine, 2023)
Objective: To report the strategies and short-term results of different treatment methods for abdominal aortic stent graft infection. Methods: Six consecutive patients (5 males and 1 female; mean age: 64 years; age range: 49-79 years) received surgical treatment for stent graft infection from November 2021 to December 2022. All patients underwent endovascular aortic repair (EVAR) for abdominal aortic and iliac artery disease, subsequently developed graft infection and then received corresponding surgical treatment with different materials (artificial blood vessel, bovine pericardium, autologous great saphenous vein) in our department. The outcomes were analysed. Results: Immediate technical success was achieved intraoperatively in all six patients. The 30-day mortality rate was 0%. During a mean follow-up of 4 months (range, 3–13 months), one patient underwent a second operation due to vascular anastomotic haemorrhage and underwent bilateral limb amputations due to ischaemia. All patients survived. Conclusions: In the short term, the different materils and methods used to treat aortic stent graft infection achieved satisfactory results.